Lagi na lamang ba akong babae? - Bernal, Ishmael; Nardes,Orlando; Regal Films ([Manla] Regal Films, 1978)
A lovely rural girl went to Manila to look for greener pastures. He worked as a restaurant waitress and a night club dancer. She was a mistress to three rich men. In the end, she was reunited with his childhood boyfriend.
DVD
Direction: Ishmael Bernal ; Executive producer: Lily Monteverde ; Story/Screenplay: Orlando Nadres ; Cinematography: Arnold Alvaro ; Musical director: Vanishing Tribe.
Alma Moreno, Christopher De Leon, Bembol Roco, Mat Ranillo III, Eddie Gutierrez
Keywords: Motion pictures -- Philippines